Influence mechanism of confining pressure on the hydraulic aperture based on the fracture deformation constitutive law - Feng, Peichao; Ma, Haichun; Wang, Jingping; Qian, Jiazhong; Luo, Qiankun (Frontiers in Earth Science, 2023)
The confining pressure induces the deformation of fractures with seepage through the fracture. The seepage characteristics can reflect the deformation of the hydraulic aperture. We propose theoretical models to describe the mechanism by which the confining pressure influences the hydraulic aperture based on the fracture deformation constitutive law models of Goodman, Bandis, Sun, and Rong. Hydromechanical testing data were used to validate the four types of proposed models,. and the fitting results show that The experiment results reveal the confining pressure and hydraulic aperture model based on Sun’s model of the fracture deformation constitutive law describe Sun’s exponential model describes the mechanism the best. The maximum hydraulic aperture closure deformation and initial hydraulic aperture go through a growth phase with a decreasing rate, and then, they enter a stability phase when the flow rate increases to 7 mL/min, while the normal stiffness of the fracture decreases to a certain value and then tends to a stable value. Flow rate decreases as confining pressure increases in a nonlinear progression, which is described by Sun’s exponential model well. We further found that in laboratory tests at various temperatures and in field tests, the confining pressure’s influence on the hydraulic aperture is highly consistent with the model based on Sun’s model. The model developed in this study describes the mechanism by which the confining pressure influences the hydraulic aperture, and it is meaningful to rock seepage engineering with in-situ stress changes at different temperatures.